EFFICACY OF FUNGICIDES, BIOCONTROL AGENTS AND BOTANICALS AGAINST ALTERNARIA LEAF BLIGHT (Alternaria sesami) IN SESAME CROP - S.L. BHATTIPROLU; P. LAKSHMI PRAVALLIKA; K. RADHIKA; M. RAGHAVENDRA (The Journal of Research ANGRAU, 2023)
Seed borne fungus, Alternaria sesami associated with sesame is the most destructive pathogen. Laboratory experiment was carried out during Dec.,2017 to Nov., 2018. The fungicides viz., hexaconazole @ 0.2% and combination product of carbendazim 12% + mancozeb 63% @ 0.2%, bio-control agents viz., Trichoderma viride @ 10 g/kg and Pseudomonas fluorescens @ 10 g/kg seed and botanicals viz., garlic clove extract 10% and neem leaf extract 10% against Alternaria blight of sesame var. YLM-17 in pot culture showed that seed treatment with combination product of carbendazim 12% + mancozeb 63% @ 0.2% was effective in reducing the per cent disease index (PDI) of Alternaria blight by 63.20 per cent and improving plant height (44.11 cm), number of capsules per plant (12.53), seed yield per plant (2.23 g) and harvest index (14.17%) when compared to control (without seed treatment). Hexaconazole, T. viride and garlic clove extract recorded 53.12%, 47.48% and 35.90% decrease in PDI, respectively. Sesame seed collected from the pots treated with carbendazim 12% + mancozeb 63% @ 0.2% recorded highest seed germination (99.33%), seedling length (17.37 cm), seedling vigour index-I (1725) and seedling vigour index-II (3.97) followed by T. viride with 98.33%, 16.75 cm, 1647 and 3.54, respectively.